PPAD-W: A Novel Privacy-Preserving Authentication With Dynamic IPs Window for IoV Networks - Sarhang Jamal Ibrahim; Hakem Beitollahi (IEEE Access)
The proliferation of Internet of Vehicles (IoV) has revolutionized transportation systems. However, ensuring secure and privacy-preserving communication in IoV networks remains a challenge. Existing authentication protocols often compromise privacy, incur high computation costs, or are vulnerable to DDoS attacks. To address these limitations, we propose a novel secure protocol for IoV networks, inspired by the Pretty Good Privacy (PGP) protocol. Our protocol leverages anonymous credentials with trust management for privacy-preserving authentication and a dynamic IP window for robust DDoS mitigation. This approach achieves a balance between security and efficiency. Through extensive simulations using Crossware ARM and OMNeT++, we demonstrate that PPAD-W achieves an average of 28.5% and 50% reduction in communication and computational costs, respectively, compared to state-of-the-art alternatives. Furthermore, the protocol effectively mitigates DDoS attacks. These results highlight PPAD-W as a promising solution for resource-constrained IoV devices, offering a compelling balance of security, privacy, and efficiency.